Azathioprine hypersensitivity presenting as septic shock with encephalopathy. - James, A; Blagojevic, J; Benham, S; Cornall, R; Frater, J (2013)
We present a case of azathioprine hypersensitivity presenting as septic shock with associated encephalopathy. The patient was presented with rapid onset of fever, hypotension, confusion and a rapidly declining conscious level. He was admitted to the intensive care unit where he received numerous invasive investigations and treatments with broad-spectrum antibiotics, antivirals and antifungals. All microbial cultures were negative. The patient-consistent with azathioprine hypersensitivity-made a spontaneous recovery after 7 days. The case shows that a time line of drug initiation is a key part of the medical history and consideration of azathioprine hypersensitivity could avoid unnecessary interventions and excessive antimicrobial use.